Strong positive correlations were found between muscle activation and breaststroke speed measured with 3d automatic tracking - Olstad, B. H.; Zinner, C.; Cabri, J.; Haakonsen, D.; Kjendlie, P. L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: A limited number of studies have investigated the muscle activation during breaststroke swimming through the use of surface electromyography (sEMG). No previous studies have investigated kinematic variables in human swimming using motion capture (mo-cap) 3D with automatic tracking (AT). The aim of this study was therefore to investigate the relationship between muscle activation in eight different muscles and swimming velocity at five different efforts. Methods: Four swimmers (one male, world championship medalist and three females, one Olympic medalist, one national medalist and one national finalist) performed one trial of 20m breaststroke at the speeds of 60%, 70%, 80%, 90% and 100% of maximum effort. During each trial the velocity of the swimmers right trochanter major and the muscle activation in biceps brachii, triceps brachii, trapezius (pars descendens), pectoralis major (pars clavicularis), rectus femoris, biceps femoris, tibialis anterior and gastrocnemius were recorded over three stroke cycles. Each stroke cycle started when the heels were fully pulled up, flexed and ready to kick. 3D images with AT were recorded from ten underwater mo-cap cameras (Oqus Underwater, Qualisys, Gothenburg, Sweden). The cameras recorded spherical markers (diameter of 19mm) fixed to the swimmers suit using cyan LED light. The muscle activity was recorded using waterproof electrodes and active sensors from (Plux Ltda, Lisbon, Portugal) and recorded according to (Olstad et al., 2011). Results: Pearson`s correlations was used to assess the relationship between the average velocity of trochanter major (representing hip speed) at the five different velocities with the average sEMG during the three stroke cycles. Strong positive and significant relationships were found for tibialis anterior r=.756 (p<0.001), biceps femoris r=-.666 (p<0.001), pectoralis major (pars clavicularis) r=.666 (p<0.001), biceps brachii r=.641 (p<0.002), triceps brachii r=-.622 (p<0.01). Positive but insignificant relationship was found for rectus femoris r=.448. Moderate positive and insignificant relationships was found in gastrocnemius r=.311. In trapezius (pars descendens) weak and insignificant relationship was found, r=-.028. Discussion: The study showed a strong and significant relationship between muscle activation in five different muscles and average swimming velocity over five different speeds. It showed that velocity can be tracked using 3D AT and therefore opens up new possibilities for conducting kinematic analysis in swimming with 3D AT combined with measuring muscle activity through the use of sEMG.